Retinoic acid receptor gamma is targeted by microRNA-124 and inhibits neurite outgrowth. (February 2020) - Su, Xiaohong; Gu, Xi; Zhang, Zhiduo; Li, Weipeng; Wang, Xuemin
Abstract: During brain development, neurite outgrowth is required for brain development and is regulated by many factors. All-trans retinoic acid (RA) is an important regulator of cell growth and differentiation. MicroRNA-124 (miR-124), a brain-specific microRNA, has been implicated in stimulating neurite growth. In this study, we found that retinoic acid receptor gamma (RARG) expression was decreased, whereas miR-124 expression was increased during neural differentiation in mouse Neuroblastoma (N2a) Cells, P19 embryonal carcinoma (P19) cells, and mouse brain, as detected by immunoblotting or RT-qPCR. And we proved that miR-124 inhibited RARG expression by binding to the 3′ UTR of RARG with a luciferase reporter assay. Upregulation of miR-124 (using miR-124 overexpressing plasmid and miR-124 mimic) led to a significant decrease in RARG protein in N2a cells and primary neurons. Therefore, we asked whether and how the miR-124/RARG axis regulates neuronal outgrowth, which is poorly understood. Strikingly, RARG knockdown by shRNA stimulated neurite growth in N2a cells and primary neurons, whereas RARG overexpression (without 3′ UTR) inhibited neurite growth in N2a cells, P19 cells, and primary neurons. Furthermore, RARG knockdown could partially eliminate neurite outgrowth defects caused by the inhibitor of miR-124, while RARG overexpression could reverse the neurite outgrowth enhancing effect of the upregulation of miR-124. Collectively, the data reveal that miR-124/RARG axis is critical for neurite outgrowth. RARG emerges as a new target regulated by miR-124 that modulates neurite outgrowth, providing a novel context in which these two molecules function. Highlights: RARG is a target for miR-124-dependent expression regulation. RARG expression is decreased during neuronal differentiation. MiR-124/RARG axis is involved in neurite outgrowth.